High‐energy collision‐induced dissociation of [M+Na]+ ions desorbed by fast atom bombardment of ceramides isolated from the starfish Distolasterias nipon. (26th January 2013) - Yoo, Ji Sun; Park, Taeseong; Bang, Geul; Lee, Chulhyun; Rho, Jung‐Rae; Kim, Young Hwan
Abstract : Ten ceramides and four cerebrosides were extracted from the starfish Distolasterias nipon by solvent extraction, silica gel column chromatography and reversed‐phase high‐performance liquid chromatography. Structural identification was conducted using tandem mass spectrometry of monosodiated ions desorbed by fast atom bombardment. The complete structures of four cerebrosides were determined by a previously reported method. The high‐energy collision‐induced dissociation (CID) spectral characteristics of ceramides with various structures depend on the number and positions of double bonds on both the N ‐acyl and sphingoid chains, the presence of a hydroxyl group or a double bond at the C‐4 position of the sphingoid chain and the presence of an α‐hydroxy group on the N ‐acyl chain. The high‐energy CID of the monosodiated ion, [M+Na] +, of each ceramide molecular species generated abundant ions, providing information on the composition of the fatty acyl chains and sphingoid long‐chain bases. Each homologous ion series along the fatty acyl group and aliphatic chain of the sphingoid base was used for locating the double‐bond positions of both chains and hydroxyl groups on the sphingoid base chain. The double‐bond positions were also confirmed by the m/z values of abundant allylic even‐ and odd‐electron ions, and the intensity ratio of the T ion peak relative to the O ion peak. This technique could determine the complete structures of ceramides and cerebrosides in an extract mixture and has great potential for determining other sphingolipids isolated from various biological sources. Copyright © 2013 John Wiley & Sons, Ltd.